Multivalent electrolyte induced surface ordering and solution self-assembly in anionic surfactant mixtures: Sodium dodecyl sulfate and sodium diethylene glycol monododecyl sulfate - Li, P; Wang, Z; Ma, K; Chen, Y; Yan, Z; Penfold, J; Thomas, RK; Campana, M; Webster, JRP; Washington, A (Elsevier, 2020)
The formation of surface multilayer structures, with the addition of multivalent electrolytes, has been observed in a range of different anionic surfactants; and notably the sodium oxyethylene glycol alkyl sulfate, SAES, and alkyl ester sulfonate, AES, surfactants. The addition of increasing amounts of AlCl3 results in increasing surface layering, with a transition from monolayer to bilayer to ultimately more extended multilayer structures at the interface.